Trends in fatalities from road traffic injuries and associated factors of patients admitted to the emergency department of St. Luke Hospital, South West Shewa Zone, Ethiopia - Beyera, Teshale Merga; Serbessa, Sheleme Duga; Fetensa, Getahun; Woldemichael, Kifle (Frontiers in Disaster and Emergency Medicine, 2024)
Introduction: Road traffic injury is a major global public health problem. It is a fatal or nonfatal injury resulting from a road traffic accident involving at least one moving vehicle on a path or road open to public traffic. Therefore, this study aimed to determine the trend and fatality of road traffic injury and associated factors of patients admitted to the emergency departments of St. Luke Hospital. Methods: An institution-based cross-sectional study was conducted from July 10 to 30, 2019. The trend of road traffic injury was conducted monthly bases from January 1, 2018, to December 31, 2018. A total of 364 road traffic-injured victim records were included. A simple random sampling technique was used for record selection. A structured data abstraction format was used to gather the required data. Binary logistic regression and multivariate logistic regression to determine the association between the outcome and explanatory variables.Adjusted odds ratios at 95% confidence intervals were used to report independent variables.The average annual road traffic injury fatality was 8.34% deaths/month. The magnitude of road traffic injury fatalities was 8.79%. Of all who victims visited the hospital 75.5% were male. The median age of the victims was 26 which ranged from 6 to 70. 51.6%. The identified risk factors for road traffic injury fatality were lack of ambulance for transportation to the hospital after the accident (AOR=7.093, 95%CI 1.950-25.793 P=0.003) and head injury (AOR=2.515 95%CI 1.075-5.885, P=0.034). Road traffic injury fatality is an important public health problem that needs special attention. Shortage of ambulance service for transportation and injury sites related to head injury were associated factors. So, it is important to establish and strengthen advanced pre-hospital care and an effective ambulance system for the transportation of victims of road traffic injury.